2012
DOI: 10.1105/tpc.112.101790
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roots Alter Epidermal Cell Fate through Mechanical and Reactive Oxygen Species Signaling

Abstract: A central question in biology is how spatial information is conveyed to locally establish a developmental program. Rice (Oryza sativa) can survive flash floods by the emergence of adventitious roots from the stem. Epidermal cells that overlie adventitious root primordia undergo cell death to facilitate root emergence. Root growth and epidermal cell death are both controlled by ethylene. This study aimed to identify the signal responsible for the spatial control of cell death. Epidermal cell death correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
144
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 47 publications
1
144
0
Order By: Relevance
“…Much is unknown about the perception of stimuli that are mechanical in nature, such as touch, gravity, and membrane stretch (i.e., mechanotransduction), though it is clear that these types of signals are important regulators of growth and development in bacteria, plants, and animals (Nakayama et al, 2012;Steffens et al, 2012;Lai et al, 2013;Mousavi et al, 2013;Yan et al, 2013). A particularly well-studied molecular mechanism for the perception and transduction of mechanical signals is provided by mechanosensitive (MS) ion channels, channels that open directly or indirectly in response to membrane tension (Arnadóttir and Chalfie, 2010;Kung et al, 2010;Sukharev and Sachs, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Much is unknown about the perception of stimuli that are mechanical in nature, such as touch, gravity, and membrane stretch (i.e., mechanotransduction), though it is clear that these types of signals are important regulators of growth and development in bacteria, plants, and animals (Nakayama et al, 2012;Steffens et al, 2012;Lai et al, 2013;Mousavi et al, 2013;Yan et al, 2013). A particularly well-studied molecular mechanism for the perception and transduction of mechanical signals is provided by mechanosensitive (MS) ion channels, channels that open directly or indirectly in response to membrane tension (Arnadóttir and Chalfie, 2010;Kung et al, 2010;Sukharev and Sachs, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Adventitious roots can form via de novo meristem initiation or the emergence of preexisting root primordia. In the case of adventitious root emergence at lower stem internodes of flooded rice, the process involves signal transduction within the growing root and the overlying epidermal cells Sauter, 2009, 2010;Steffens et al, 2012). It was shown that in the adventitious root primordium, ethylene-and ROS-dependent signaling orchestrated the promotion of growth by signaling via mechanical force to the overlying epidermal cells.…”
Section: Morphological and Anatomical Adaptations That Increase Floodmentioning
confidence: 99%
“…Although microarray studies revealed that the epidermal cells overlaying root primordia have a very distinct cellular identity (Steffens and Sauter, 2009), the precise signal that caused only these specific cells to die remained unknown. It is now clear that this trigger is the mechanical stimulus provided by the underlying root primordia when they start growing (Steffens et al, 2012). The growing ARs exert a mechanical force on the epidermal cells overlying them in a process that also requires ethylene-mediated ROS formation (Fig.…”
Section: Ethylene-mediated Flooding-adaptive Traitsmentioning
confidence: 99%